Knowledge of Cervical Cancer Screening in Adult Women: Meta-Analysis - I Gusti Agung Ngurah Putra Pradnyantara; Indah Adhitama Chrisnanda (Journal of Epidemiology and Public Health, 2022)
Background: Cervical cancer is the fourth common cancer worldwide and the second most common cancer cases in women. Cervical cancer screening allows detection of abnormal cervical cells. Having knowledge about cervical cancer and its screening can increase the absorption of services for cervical cancer screening. This study was aimed to determine the comparison of participation in cervical cancer screening in adult women with high education with adult women with low education. Subjects and Method: This study was a systematic review and meta-analysis with the following PICO, population: adult women. Intervention: high knowledge. Comparison: low knowledge. Results: cervical cancer screening. The articles used in this study were obtained from two databases, namely Google Scholar and Pubmed. Keywords to search for "Knowledge," "screening" "cervical cancer" "adult women". The articles included are full-text articles with a cross-sectional study design from 2016 to 2022 and report multivariate analysis with Adjusted Odds Ratio (aOR). Articles were analyzed using the Review Manager 5.3 application. Results: Systematic study and meta-analysis of this study A total of 16 articles from 2 African continents (Ethiopia, Nigeria, Southern Ethiopia, South west Ethiopia, Ivory Coast, South Africa, Northwest Ethiopia, Cameroon, eastern Ethiopia, Ghana), and Asia (Thailand and Malaysia). Showed that women with high knowledge had an attitude to cervical cancer screening 3.63 times compared to women with low knowledge and the results were statistically significant (aOR = 3.63; 95% CI = 2.11 to 6.24; p<0.001). Conclusion: A high level of knowledge increases attitudes to cervical cancer screening in adult women. Keywords: screening, cervical cancer, knowledge. Correspondence: I Gusti Agung Ngurah Putra Pradnyantara, Poltekkes Permata Indonesia. Jl. Ringroad Utara No 22 C, Gandok, Condong Catur, Depok, Sleman, Yogyakarta, Indonesia. Email: gustipradnyantara1997@gmail.com. Mobile: +6282146804776.